Dissipation and discretization in time marching CFD calculation - Alimin, E. K. (Cranfield University, 1995)
This thesis concentrates on accuracy improvements for an existing software package that solves the three dimensional Reynolds Averaged Navier-Stokes equations in rotating coordinates. It is a cell centred explicit time marching code. Two topics are considered: improvement to the discretization scheme, and reduction of the artificial dissipation. The first topic is the analysis of the straight averaging process which demonstrates that the process can result in inconsistency with a skewed grid. An alternative consistent scheme is proposed which is based upon quadratic interpolation. Improved accuracy can also be obtained by modifying the grid or adopting a cell vertex scheme. The stability of the iterative process is also shown to depend on the time step. The reduction of artificial dissipation (second topic) first considers the role of the so called aspectratio and velocity functions. These are found to be limited in influence and a new function is proposed based upon the local flow gradient. Both two and three dimensional turbomachinery cases are tested and improvements demonstrated. In the second part of the analysis, the eigenvalues of the stability matrix are used to reduce the dissipation in overdamped regions. Again this method is applied to various test cases and improvements demonstrated. The management part of this Total Technology PhD Program discusses topics concerned with collaboration and technology development in the aero engine industry with particular emphasis on the role of an "emerging" partner.